Prehospital nurses' participation in research: benefits for the clinical practice - Mauro Mota; Margarida Reis Santos; Regina Pires; Isabel Bica; Madalena Cunha (RevSALUS)
Introduction: Nurses' participation in data collection is crucial to the development of nursing research. The contributions are also important in the introduction of updated scientific knowledge into the clinical practice. Objective: To assess the views of pre-hospital nurses on the impact that their participation in data collection for a research study had on their clinical practice. Methods: This was a descriptive, cross-sectional, quantitative study conducted with pre-hospital nurses who participated in data collection for a fourteen-month investigation in Portugal. A questionnaire specifically designed for this purpose was provided to the nurses at the end of the research data collection period. Results: Nurses (n=158) from every region of Portugal took part in the assessment. Most of the nurses (95%; n=150) found that their participation in the research was extremely important or very important to deepen their theoretical knowledge and improve the quality of their practices. As for the impact that their participation in the research had on their current performance, most of the nurses found it extremely important [Score=5; 60%, n=95]. Conclusion: It is important that strong collaborative relationships are established between academia and clinical practice to develop and optimize nurses' interventions in pre-hospital rescue. Many of the nurses had never participated in any data collection before, and their participation allowed them to optimize this procedure and understand the importance of their participation in each phase of the research. Their opinion suggests a very important contribution to increase their level of knowledge and the quality of their clinical practice.